FINITE ELEMENT ANALYSIS OF STRIP FOOTING RESTING ON GIBSON-TYPE SOIL BY USING MATLAB (Journal of Engineering, 2011)
This research presents a method of using MATLAB in analyzing a nonhomogeneous soil (Gibson-type) byestimating the displacements and stresses under the strip footing during applied incremental loadingsequences. This paper presents a two-dimensional finite element method. In this method, the soil is divided into a number of triangle elements. A model soil (Gibson-type) with linearly increasing modulus of elasticity with depth is presented. The influences of modulus of elasticity, incremental loading, width of footing, and depth of footing are considered in this paper. The results are compared with authors' conclusions of previous studies.